2004
DOI: 10.1007/s00192-004-1128-x
|View full text |Cite
|
Sign up to set email alerts
|

A study of quality of life in primigravidae with urinary incontinence

Abstract: This study aimed to establish the prevalence and effect of urinary incontinence on quality of life during pregnancy and after parturition. A prospective cohort of primigravidae was recruited. The Kings Health Questionnaire (KHQ) was self-administered antenatally (34 weeks to term) and postnatally (3 months after delivery). Four hundred ninety-two primigravidae were recruited. The prevalence of urinary incontinence was reported as: pre-pregnancy 3.5% (17/492), antenatal 35.6% (175/492), 3-5 days postpartum 13.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
6
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 13 publications
(22 reference statements)
3
79
6
4
Order By: Relevance
“…", most NG women answered "not at all" while HG women responded "a little". This is in agreement with Dolan et al [34], who used the KHQ to establish the prevalence and effect of urinary incontinence on quality of life during pregnancy and after parturition. They concluded that most women with urinary incontinence experience minimal impact on quality of life during pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…", most NG women answered "not at all" while HG women responded "a little". This is in agreement with Dolan et al [34], who used the KHQ to establish the prevalence and effect of urinary incontinence on quality of life during pregnancy and after parturition. They concluded that most women with urinary incontinence experience minimal impact on quality of life during pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…52 Some studies have shown a low impact on the quality of life of women with UI; however, they were conducted during pregnancy or in the first year postpartum. 53,54 This difference in results might be associated with the fact that the women in these situations see UI as an expected disorder for such situations instead of considering it a disease. Córcoles et al, studying 126 women with SUI, demonstrated impairment in their quality of life with gradual deterioration as they got older.…”
Section: Discussionmentioning
confidence: 96%
“…55 The questionnaire known as The Kings Health Questionnaire (KHQ) has been used in several studies assessing the quality of life and UI. 54,55 A study comparing the ICQ-SF with the KHQ has been conducted and showed that both have similar sensitivity and specificity, and the ICQ-SF was considered to have better applicability because it has fewer questions. 56 …”
Section: Discussionmentioning
confidence: 99%
“…Lower prevalence estimates are reported in other cohorts; Dolan et al investigated prevalence of any UI in week 32 to term in a cohort of 492 nulliparous women in England (Dolan et al, 2004). Prevalence of UI was 36 % in pregnancy.…”
Section: Prevalence Of Urinary Incontinence In Pregnancymentioning
confidence: 95%